CAL (computer assisted) learning for English idioms / Tan Yee Loon - Tan , Yee Loon (2001)
CAL for English Idioms is a multimedia educational courses are designed for beginning English learners. It covers a large collection of English idioms and will let the users learn the meaning of English Idioms, and know how to use them. It is interactive and it uses multimedia elements to encourage learning through interaction between the computer and the user. CAL for English Idioms includes three major functional modules:Learning, Interactive and Quiz and Test.The Learning Module integrated text, graphics, animation and video to aid learning,whereas the Interactive module compliments the Leaming by providing interactive games to enhance the user's memory about the Idioms. The Quiz and Test Module however comprises multiple-choice questions that are graded automatically. CAL for English Idioms aims to recover the lack of the teaching aid in school. CAL for English Idioms is developed using Microsoft Visual Basic 6.0. It is a powerful tool and possesses the basic features to implement the application, such as images, sounds and animations. Further more, Visual Basic has a strong screen design capability that enables the process of interface design, interface editing, and prototyping significantly easier. The rapid application development (RAD) approach was adopted throughout the development of this project.